DISAGREEMENT STRATEGIES USED BY INTROVERT AND EXTROVERT STUDENTS OF ENGLISH STUDY PROGRAM UNIVERSITAS BRAWIJAYA - TATYAMANI, AISYAH NABILA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Speech Acts, Disagreement Strategies, Introvert, Extrovert, DiscourseCompletion Test (DCT). Expressing disagreement is considered as dis-preferred act during daily interactions. The writer conducted a study about disagreement strategies used by introvert and extrovert students of English Study Program Universitas Brawijaya which portrays disagreement situations within campus environment. There were two problems to be solved in this study, namely: (1) what strategies do introvert students of English Study Program Universitas Brawijaya employ to express disagreement and (2) what strategies do extrovert students of English Study Program Universitas Brawijaya employ to express disagreement.  The method of this study was qualitative approach using survey. The writer used two kinds of questionnaires as the instrument to collect the data, namely: (1) Personality Type Questionnaire and (2) Discourse Completion Test (DCT). The participants of this study were 12 students of 2012 Batch of English Study Program Universitas Brawijaya. This study revealed that both the introvert and extrovert students mostly used the same strategies; however, the use of the strategy to express disagreement was different during certain situations. Furthermore, the study also found that in facing disagreement, situational context might also influence in the selection of the strategies. This study was also able to discover new types of Act Combinations strategies namely, Challenges followed by Contradictions (CH+CT) and Challenges followed by Counterclaims (CH+CC) which could not be found in either previous studies or Muntigl & Turnbull’s study.The writer suggested next researchers investigate the factors that influence disagreement strategies from different aspects such as social status, gender, ethnic, etc. The next researchers could also investigate another strategy under the branch of speech acts such as, compliment strategies, refusal strategies, etc.